Pengaruh Pelatihan dan Motivasi Kerja Terhadap Turn Over Karyawan di Pusat Pelatihan BIPTAK Kota Semarang - Yoki Nawan Gunara; Umi Fadlilah Hidayanti; Heru Yuliyanto (Dharma Ekonomi, 2024)
This study aims to analyze the influence of training and work motivation on employee turnover at the BIPTAK Training Center in Semarang City. Employee turnover is a challenge for organizations as it can affect stability and work productivity. This research employs a quantitative approach using multiple linear regression analysis to examine the relationship between the independent variables—training and work motivation—and the dependent variable—employee turnover. The findings indicate that training has a negative and significant effect on employee turnover, meaning that the better the training provided, the lower the employee turnover rate. Additionally, work motivation also has a negative and significant effect on employee turnover, suggesting that the higher the work motivation, the lower the likelihood of employees leaving the company. These findings highlight the importance of improving training programs and motivation strategies to reduce employee turnover rates within organizations.